Dos impactos à conservação de fauna: a implantação do campus Lagoa do Sino e a incidência de atropelamentos de animais silvestres - Cravo, Adriana Paula Bernardo (2018)
In 2012, the new UFSCar campus Lagoa do Sino was implemented in the southwest of the state of São Paulo, close to the cities of Campina do Monte Alegre and Buri. The activities started in 2014, when the first students and staff arrived to study and work. However, it is located in an area with low HDI (Human development index), so Campina do Monte Alegre had to adapt to this new population very quickly, without the necessary services and structure. Even with low social and economic indexes, the area is one of the most conserved in the state, with many national and state parks. Considering this new scenario, the amount of reported road killed animals was increasing. For this reason, our goals were to (1) study this problem through 74km of the road SP-189 (from Raposo Tavares road to Buri, crossing Campina do Monte Alegre and the new campus), (2) map the road killing hotspots, (3) identify the season with higher levels of accidents and (4) characterize the adjacent landscape through a 5km-extension buffer. During one year (July/2016- June/2017), we monitored the road once a week looking for road killed animals. We found 172 killed animals and 158 of them were wild. The majority of them were birds (69), followed by mammals (44), reptiles (23) and amphibians (22). The most common group was wild dogs (Cerdocyon thous and Lycalopex vetulus) (11 animals) while the only vulnerable species, according to IUCN, was the giant anteater (Myrmecophaga tridactyla - 3 animals found). The most frequent landscape was crop rotation (bean, corn, wheat) (28%), followed by fragmented vegetation (20%), pasture (18%) and forestry (14%), suggesting a very anthropized area with no predominant landscape. The road killing during the rainy season (spring and summer) were significantly higher than those reported in the dry season (autumn and winter). Birds and reptiles’ roadkilling were also significantly different between the two seasons. Additionally, two of the three hotspots found were in the two extremities of Campina do Monte Alegre, suggesting a direct influence from the vehicles movement from UFSCar students and staff, and the third hotspot was identified between Raposo Tavares road and this city. According to the spatial estististics analysis, we confirmed that there is a stronger influence of the urban area on the incidence of the hotspots. The results were applied in two different activities to mitigate the impacts of roadkilling in wild animals. The first one was an educational activity with the children of a public school in Campina do Monte Alegre to raise awareness about the threats to wildlife conservation, while the second measure was a partnership with the city hall of Campina do Monte Alegre in order to decrease the accidents envolving wild animals in the two hotspots near the city. Therefore, this kind of work is extremely important to identify the real problems of the area and also to implement effective and viable solutions.